Napoleon Dynamite [videorecording (DVD)] - Hess, Jared, 1979-; Heder, Jon, 1978-; Gries, Jon, 1957-; Ruell, Aaron (20th Century Fox Home Entertainment, 2004)
Napoleon is a new kind of hero, complete with a tight red 'fro, sweet moon boots, and skills that can't be topped. Napoleon spends his days drawing mythical beasts, duking it out with his older brother, Kip, and trying to avoid his scheming Uncle Rico. When two new friends enter Napoleon's life - shy Deb and mustachioed Pedro - the trio launches a campaign to elect Pedro for class president and make the student body's wildest dreams come true. But if Pedro is to beat stuck-up Summer, Napoleon will have to unleash his own secret weapon.